Sociocultural space of the Penza region during the Great Patriotic War (1941-1945) - Yakupova, Dar'ya Viktorovna (Исторический журнал: научные исследования, 2023)
The subject of the research is the study of the content, forms and methods of practical activity of cultural organizations, associations of the Penza region and creative workers during the Great Patriotic War at the front and in the rear, as well as socio-cultural interaction in order to form patriotic sentiments. Special attention is paid to the coverage of the activities of cultural institutions of the Penza Region, creative associations, as well as the work of the authorities to achieve the goals and objectives of ensuring the preservation of a high level of socio-psychological motivation of the Soviet population in the fight against the Nazi invaders.The study is also a collection, generalization and updating of local history material on the transformation of cultural life of the Penza region caused by evacuation processes. Within the framework of the work, new historical sources that were not previously involved in scientific circulation are published, to study the socio-cultural space and creativity of cultural figures of the Penza region during the Great Patriotic War as a system of interaction and education of patriotism, adaptation strategies of the Soviet man in the conditions of mobilization and extreme living conditions. The thesis is substantiated that the response of art workers to the needs of wartime was not just a formal execution of a state order, but an internal call, a philosophically grounded meaningful action of each employee. It was the inner desire to be useful during the war, coupled with creative potential and a sincere desire for self-realization, that became a vivid example of the manifestation of spiritual and moral values traditional for our Fatherland. The material collected and analyzed in the work can be used in research work, in the preparation of teaching aids, in university and school training courses, including local history, as well as in the work of museums and in the preparation of scientific literature. The methodological basis of the work was logical, historical-logical, system-structural, socio-cultural, comparative-legal, generalization, commenting method.